2009
DOI: 10.1073/pnas.0805845106
|View full text |Cite
|
Sign up to set email alerts
|

Predicting spatial similarity of freshwater fish biodiversity

Abstract: A major issue in modern ecology is to understand how ecological complexity at broad scales is regulated by mechanisms operating at the organismic level. What specific underlying processes are essential for a macroecological pattern to emerge? Here, we analyze the analytical predictions of a general model suitable for describing the spatial biodiversity similarity in river ecosystems, and benchmark them against the empirical occurrence data of freshwater fish species collected in the Mississippi-Missouri river … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…C in Šizling et al 2009b for a detailed explanation). Unlike in the other two data sets, some examined plots were not adjacent in the bird survey, with gaps of up to 200 m. Longer interplot distances, however, should make the Jaccard index between those plots lower (due to distance decay in community similarity; e.g., Nekola and White 1999;Azaele et al 2009) and thus make z higher. Hence, the true z values for birds should be lower than those plotted, which further accentuates the differences between the z-D relationships of the three groups, making our test conservative.…”
Section: Data Testsmentioning
confidence: 91%
“…C in Šizling et al 2009b for a detailed explanation). Unlike in the other two data sets, some examined plots were not adjacent in the bird survey, with gaps of up to 200 m. Longer interplot distances, however, should make the Jaccard index between those plots lower (due to distance decay in community similarity; e.g., Nekola and White 1999;Azaele et al 2009) and thus make z higher. Hence, the true z values for birds should be lower than those plotted, which further accentuates the differences between the z-D relationships of the three groups, making our test conservative.…”
Section: Data Testsmentioning
confidence: 91%
“…This is even more striking when highlighting the gross simplifications that we assumed in the model: translational and rotational invariance that are generally violated in natural populations; smoothed geometry of the study region; temporal stationarity; and a simple form for the pair correlation function. Had we employed more general, yet realistic, functions (e.g., see Azaele et al 2009) for this latter, we would likely have obtained even more satisfactory results. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies on macroinvertebrate populations in New Zealand streams found that population structure was better explained by a combination of local and regional forces rather than by any scale-specific set of processes individually (Thompson & Townsend, 2006). Because high dispersal rates are often sufficient to swamp the effects of local population dynamics, other investigations found that fish community dynamics in the Mississippi-Missouri drainage could be modelled with only regional dispersal-driven processes (Azaele, Muneepeerakul, Maritan, Rinaldo, & Rodriguez-Iturbe, 2009;Convertino et al, 2009;Muneepeerakul et al, 2008). Because high dispersal rates are often sufficient to swamp the effects of local population dynamics, other investigations found that fish community dynamics in the Mississippi-Missouri drainage could be modelled with only regional dispersal-driven processes (Azaele, Muneepeerakul, Maritan, Rinaldo, & Rodriguez-Iturbe, 2009;Convertino et al, 2009;Muneepeerakul et al, 2008).…”
Section: F I G U R Ementioning
confidence: 99%